Polylactide-co-glycolide nanoparticles immobilized with isoniazid: optimization using the experimental Taguchi method - Galiyeva, A.R.; Tazhbayev, Ye.M.; Zhumagaliyeva, T.S.; Sadyrbekov, D.T.; Kaikenov, D.A.; Karimova, B.N.; Shokenova, S.S. (KU Publ., 2022)
The research aims to optimize and minimize the number of experiments to obtain polylactide-co-glycolide (PLGA) nanoparticles (NPs) immobilized with antituberculosis (anti-TB) drug — isoniazid (INH) by applying the Taguchi method and Design Expert statistical software. Several experiments were performed with varying parameters, namely polymer/drug ratio, polyvinyl alcohol (PVA) concentration, the ratio of organic solvent to the aqueous phase, and solvent type. Three different levels and a fractional factorial design were derived for each parameter, particularly the standard orthogonal array (OA) L9. Drug-loaded nanoparticles were prepared by the double emulsion method. The results were obtained from 9 runs indicated particle sizes ranging from 152.2±6.4 nm to 496.4±9.5 nm. These results were used to predict the optimum conditions for synthesizing INH-PLGA particles. The calculated data correlate well with the experimental data. INH-PLGANPs were obtained with a mean size and polydispersity of nanoparticles of 152.2±2.25 nm and 0.279±0.03, respectively. Scanning electron microscopy, thermogravimetric analysis, and differential scanning calorimetry were carried out to characterize the obtained nanoparticles. The degree of drug release from PLGA NPs was studied, and the results showed that PLGA prolonged the release of INH from the polymer matrix.
Изониазидпен иммобилизацияланған полилактид-со-гликолид нанобөлшектері: Тагучи эксперименттік әдісінің көмегімен оңтайландыру
Наночастицы полилактид со-гликолида, иммобилизованные изониазидом: оптимизация с помощью экспериментального метода Тагучи
Keywords: isoniazid; nanoparticles; Taguchi method; polylactide-co-glycolide; double emulsion; anti-TB drug; experimental design; biopolymers